13C-NMR glycosylation effects in (1→3)-linked furanosyl-pyranosides. (19th November 2015) - Gerbst, Alexey G.; Krylov, Vadim B.; Vinnitskiy, Dmitry Z.; Dmitrenok, Andrey S.; Shashkov, Alexander S.; Nifantiev, Nikolay E.
Highlights: Six (1→3)-linked furanosyl-pyranosides have been synthesized. 13 C NMR glycosylation effects have been measured for these compounds. Several conformers have been revealed during theoretical conformational analysis. These conformers are used to explain the observed glycosylation effects. Graphical abstract: Abstract: Synthesis, theoretical conformational analysis (molecular mechanics and DFT calculations) and NMR spectral data including the 13 C-NMR glycosylation effects for six pairs of isomeric furanosyl-(1→3)-pyranosides with different anomeric and absolute configurations of furanosyl units as well as configurations of C2 and C4 in the pyranoside units are described. The determined 13 C-NMR glycosylation effects were shown to correlate with the pattern of intramolecular interactions around the inter-unit bonds.